Treatment of hepatitis C virus infection with direct-acting antivirals plus ribavirin eliminates viral RNA from peripheral blood mononuclear cells and reduces virologic relapse in diverse hepatic parenchymal changes - Abd Alla, Mohamed Darwish Ahmed; Dawood, Reham M.; Rashed, Hassan Abd EL-Hafeth; Farrag, Galal; Ammar, Islam Abdelmawla Emran; Mahmoud, Mohamed Mahmoud Abdel-Halim; Salum, Ghada M.; Altanbouly, Ahmed Mohamed Abdulhamid; El Meguid, Mai A.; Awady, Mostafa K. El (Archives of virology, 2021)
Elimination of hepatitis C virus (HCV) may fail, leading to a non-response outcome because of inappropriate testing for viral RNA in peripheral blood mononuclear cells (PBMCs). Sequelae of HCV genotype 4 therapy with sofosbuvir and daclatasvir ± ribavirin were assessed in our study at the 12 th week after end of treatment (EOT) by screening for viral genomic RNA in serum and PBMCs with correlation to hepatic parenchymal changes. We recruited 102 out of 2165 patients who had received sofosbuvir/daclatasvir, either alone (n = 1573) or together with ribavirin (n = 592). Subjects were classified into three groups based on testing by single-step reverse transcription PCR: group I, HCV negative in both serum and PBMCs (n = 25); group II, HCV positive in PBMCs only (n = 52); and group III, HCV positive in both serum and PBMCs (n = 25). Groups I and II (n = 77) were selected out of 2102 (every 27 th subject), while group III (n = 25) were selected from every second or third serologic relapse (n = 63). The pre-sampling population (n = 2165) showed sustained virologic response (SVR) in 33.21%; serologic relapse in 2.91%; HCV RNA only in PBMCs (66.79%) compared to serologic relapses and potential cure ( P < 0.0001); higher serologic (38 out of 63, P = 0.03210) and cellular (36 out of 52, P = 0.0002) relapses in dual therapy than in triple therapy. The post-sampling population (n = 102) showed more HCV relapses in dual (50 out of 60) than in triple (27 out of 42) therapy ( P = 0.0351); increased HCV antisense RNA strand in relapses compared to positive-sense strands alone ( P < 0.001); and significant SVR events in undetectable (15 out of 31) compared to early (10 out of 55, P = 0.0058) and cirrhotic liver tissue changes (0 out of 16, P = 0.0006). In summary, HCV treatment with sofosbuvir/daclatasvir is followed by higher rates of serologic and intracellular viral RNA relapse than treatment with sofosbuvir/daclatasvir plus ribavirin. Cellular and serum viral RNA relapses are accompanied by HCV-induced hepatic pathology. An increased SVR with no detectable liver tissue changes was observed after triple therapy due to elimination of HCV RNA from PBMCs.